Jeremiah COOGAN, Eusebius the Evangelist: Rewriting the Fourfold Gospel in Late Antiquity, New York, Oxford University Press, 2023, 234 páginas, ISBN 9780197580042 (Minerva, 2023)
A review ofJeremiah Coogan, Eusebius the Evangelist: Rewriting the Fourfold Gospel in Late Antiquity, New York, Oxford University Press, 2023, 234 pages, ISBN 9780197580042